Insight into the C8 light hydrocarbon compositional differences between coal-derived and oil-associated gases - Guoyi Hu; Weilong Peng; Cong Yu (Journal of Natural Gas Geoscience, 2017)
To analyze the C8 light hydrocarbon of absorbed gas in the source rock and natural gas, both the PY-GC and GC were applied. This is done in order to develop the discrimination parameters of different genetic gases. Eight samples, including six mudstones with type II1 and type I organic matter and two coals, were analyzed by PY-GC. On the other hand, the sixteen typical coal-derived gases and sixteen oil-associated gases were analyzed by GC. The results show that there exists a great difference in the ratio of 2-methylheptane and 1-cis-3-dimethylcyclohexane in coal-derived gases, oil-associated gases, and source rock absorbed gases. The ratio in coal-derived gases is less than 0.5, whereas it is higher than 0.5 in oil-associated gases. In addition, there are also differences in the relative composition of C8 normal alkanes, isoparaffin, and cycloparaffin in coal-derived and oil-associated gases. Coal-derived gas is characterized by high cycloparaffin content that is generally higher than 40%, while the oil-associated gas exhibits low cycloparaffin content that generally less than 40%, as well as high isoparaffin content. Therefore, these parameters can be used to identify a coal-derived gas from an oil-associated gas. Keywords: C8 light hydrocarbons, Coal-derived gas, Oil-associated gas